The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jssr.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Role retreatism of social studies teacher-coaches: An unequal balancing act

Abstract: The current study explores role retreatism in secondary social studies teachers who coach athletics. The purpose of this study was to determine the extent to which social studies teacher-coaches retreat towards coaching and reasons for such prioritization. A case study relying primarily on interview and document data was conducted which included three secondary social studies teachers who coach football in the southeastern United States. Results indicate that participants prioritized coaching over teaching to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…As a result, the pressure to win or risk losing both teacher and coaching jobs continues (Hill, 1997;Konukman et al, 2010). In contrast to these dilemmas, some teacher-coaches state they were proud of their classroom achievements and challenged the teacher-coach stereotype (Conner, 2014;Herbert, 2007;Rodgers, 2013). Consequently, more work is needed to understand how the achievement or lack thereof of coaching can impact teachers in the classroom.…”
Section: Role Conflictmentioning
confidence: 99%
“…As a result, the pressure to win or risk losing both teacher and coaching jobs continues (Hill, 1997;Konukman et al, 2010). In contrast to these dilemmas, some teacher-coaches state they were proud of their classroom achievements and challenged the teacher-coach stereotype (Conner, 2014;Herbert, 2007;Rodgers, 2013). Consequently, more work is needed to understand how the achievement or lack thereof of coaching can impact teachers in the classroom.…”
Section: Role Conflictmentioning
confidence: 99%
“…Despite their presence in popular culture and the teacher workforce, the history of Black male teacher-coaches has been erased and replaced with a White origin story (Stacy, 2016) that does not align with the specificity of the Black male teacher-coach tradition set forth by Dr. Carter G. Woodson and Dr. Edwin B. Henderson (Henderson, 1949;Thomas, 2022b). Contemporary scholarship has primarily focused on White male participants and has framed teacher-coaches as anti-intellectuals who avoid teaching duties (Conner, 2014). Thus, Black male teachers have historically been constructed as problems for their counter-hegemonic practices, and teacher-coaches have been positioned as anti-intellectual.…”
Section: Black Male Teachers and Teacher-coachesmentioning
confidence: 99%
“…The current researchers do not attest that social studies teachers who coach are less effective teachers than those who do not. In fact, they contend there are many perceived benefits of coaching such as the ability to foster strong relationships with and among students (Conner, 2014). In an empirical study, Bowen and Greene (2012) found that a schools' commitment to athletics was positively correlated to students' academic success.…”
Section: The Social Studies Teacher-coachmentioning
confidence: 99%
“…To avoid such burnout, prior research further indicates that social studies teachers prioritize one role at the expense of the other—a phenomenon known as role retreatism . Research investigating role retreatism indicates that teacher-coaches tend to prioritize the role for which they feel most rewarded, most valued, and most accountable (Conner, 2020; Millslagle & Morley, 2004; O'Connor & MacDonald, 2002; Ressler, Richards, & Wright, 2016; Richards & Templin, 2012). The unequal rewards system SSTCs encounter contributes to their prioritization of coaching (Conner, 2020).…”
Section: Introductionmentioning
confidence: 99%